2013
DOI: 10.1038/cddis.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibitors induce tumor-cell-selective pro-apoptotic transcriptional responses

Abstract: The identification of recurrent somatic mutations in genes encoding epigenetic enzymes has provided a strong rationale for the development of compounds that target the epigenome for the treatment of cancer. This notion is supported by biochemical studies demonstrating aberrant recruitment of epigenetic enzymes such as histone deacetylases (HDACs) and histone methyltransferases to promoter regions through association with oncogenic fusion proteins such as PML-RARα and AML1-ETO. HDAC inhibitors (HDACi) are poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
130
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 51 publications
(71 reference statements)
14
130
0
1
Order By: Relevance
“…Although the reasons for the observed differences in sensitivity to panobinostat are unclear, perhaps the distinct transcriptional responses of lymphocyte subsets, progenitor populations and malignant cells instill particular resistance or sensitivity to HDACi. Indeed, we have observed that isogenic matched normal and tumour cells display subtle differences in transcriptional responses to HDACi resulting in profound differential biological responses 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the reasons for the observed differences in sensitivity to panobinostat are unclear, perhaps the distinct transcriptional responses of lymphocyte subsets, progenitor populations and malignant cells instill particular resistance or sensitivity to HDACi. Indeed, we have observed that isogenic matched normal and tumour cells display subtle differences in transcriptional responses to HDACi resulting in profound differential biological responses 53 .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] HDACi are largely ineffective as monotherapy against DLBCL as well as solid tumors, therefore, research focus has shifted to combining HDACi with other therapeutics for treatment of a variety of cancers. [8][9][10] A confounding issue in identifying effective HDACi-containing drug combinations is that a multitude of mechanisms have been attributed to the anti-cancer effects of HDACi including: alteration of gene expression, activation of pro-apoptotic pathways, induction of tumor cell differentiation, inhibition of angiogenesis, and modulation of cell cycle progression.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] A confounding issue in identifying effective HDACi-containing drug combinations is that a multitude of mechanisms have been attributed to the anti-cancer effects of HDACi including: alteration of gene expression, activation of pro-apoptotic pathways, induction of tumor cell differentiation, inhibition of angiogenesis, and modulation of cell cycle progression. 5,7,[11][12][13][14] Taking a mechanistic approach to understand the molecular effects of HDACi specifically in the DLBCL context, we developed a cell-based model of sensitivity and resistance to HDACi. The mechanistic knowledge gained from this system can be used to rationally select therapeutics which can be effectively combined with HDACi.…”
Section: Introductionmentioning
confidence: 99%
“…GLI2 is a more potent activator of BCL2 expression than GLI1, 55 which may explain the subtle transcription repression observed (1.6-fold). Bolden et al 5 previously described a tumor-cellselective pro-apoptosis gene expression signature upon vorinostat treatment of paired normal and tumorigenic human fibroblasts. Vorinostat treatment of BJ LTSTERas fibroblasts resulted in repression of BCL2L1 (BCLXL) and BCL2L2 (BCLW), which was also observed in the vorinostat-treated HCT116-VR cells in this study, indicating a potentially conserved transcriptional response to vorinostat treatment in transformed cells.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, we and others have demonstrated that overexpression of prosurvival Bcl-2-family proteins protects cells against HDACi-induced apoptosis. [3][4][5][6] HR23B has also been implicated in vorinostat resistance as a protein through which vorinostat induces apoptosis via impaired proteasome function. [7][8][9] As the identification of these mechanisms of resistance has not yet impacted the clinical use of HDACi through the generation of combination therapy approaches or clinical biomarkers, a genome-wide study was conducted to identify further mechanisms of resistance to HDACis that may improve the clinical application of these agents.…”
mentioning
confidence: 99%